Pathogen variation and genetic control of Puccinia triticina in Zimbabwe - Chiuraise, Nyashadzashe (University of the Free State, 2022)
Genetic resistance is the most cost-effective approach to manage wheat leaf rust caused by Puccinia triticina Eriks. (Pt). However, the continuous emergence of more virulent races can deplete monogenic sources of resistance. The aim of this study was to determine the distribution, race and genetic diversity of Pt isolates in Zimbabwe and to characterise the sources of resistance in selected wheat accessions. In total, 104 single pustule isolates of Pt were established from infected wheat samples that were collected from the main wheat production regions of Zimbabwe during surveys from 2019 to 2021. Results from phenotyping a set of 46 differential and additional wheat lines revealed Pt race MCDS as dominant in Zimbabwe. Genotyping of 48 Pt isolates with 19 microsatellite markers, followed by DARwin and STRUCTURE analyses, confirmed a high genetic similarity between the Zimbabwean isolates and representative isolates of the South African Pt races MCDS, MCPS and MFPS. However, five isolates (19_1_2019, 24_3_2019, 5_1_2020, 20_1_2020, 23_2_2020) with genetic similarity to South African races SDDN and SCDS were detected. The detection of the five genetically distinct Pt isolates among the Zimbabwean isolates indicates genetic variation that could have arisen from foreign introductions. The infection type (IT) data from screening the 39 differential lines and 72 Zimbabwean wheat accessions with nine Pt races were not informative in postulating the presence of any all-stage resistance genes (ASR). Forty-nine Zimbabwean varieties showed low (resistant) seedling ITs to all nine Pt races tested in the greenhouse and at least 53 varieties were strongly resistant with immune responses to races CFPS+Lr20 and MFPS in the field. From these, 25 wheat lines with ASR to all Pt race isolates were crossed with an MCDS susceptible variety. Twenty-three varieties displayed an F2 segregation ratio of 3:1, indicating the inheritance of a single dominant leaf rust (Lr) resistance gene. Molecular markers detected Lr19 in 20 of these varieties. Five adult plant resistance genes (APR) namely Lr27, Lr34, Lr37, Lr46 and Lr68 were detected in the Zimbabwean germplasm, with Lr46 being the most common and Lr34 the least common. A multi-environmental trial (MET) conducted over two seasons in Zimbabwe identified wheat varieties SC001, SC002, SC004, SC027 and SC W9101 as widely adapted with stable yields, acceptable leaf rust resistance while meeting the quality traits required in the wheat value chain. Overall, the outcomes of this study make a valuable contribution to shaping longer term strategies to control wheat leaf rust in Zimbabwe.
Thesis (Ph.D. (Plant Pathology))--University of the Free State, 2022
Keywords: Puccinia triticina; resistance gene postulation; genotyping